Hazard analysis approaches for certain small retail establishments in view of the application of their food safety management systems. (2nd March 2017) - ,; Ricci, Antonia; Chemaly, Marianne; Davies, Robert; Fernández Escámez, Pablo Salvador; Girones, Rosina; Herman, Lieve; Lindqvist, Roland; Nørrung, Birgit; Robertson, Lucy; Ru, Giuseppe; Simmons, Marion; et al.
Abstract: Under current European hygiene legislation, food businesses are obliged to develop and implement food safety management systems (FSMS) including prerequisite programme (PRP) activities and hazard analysis and critical control point principles. This requirement is especially challenging for small food retail establishments, where a lack of expertise and other resources may limit the development and implementation of effective FSMS. In this opinion, a simplified approach to food safety management is developed and presented based on a fundamental understanding of processing stages (flow diagram) and the activities contributing to increased occurrence of the hazards (biological, chemical (including allergens) or physical) that may occur. The need to understand and apply hazard or risk ranking within the hazard analysis is removed and control is achieved using PRP activities as recently described in the European Commission Notice 2016/C278, but with the addition of a PRP activity covering 'product information and customer awareness'. Where required, critical limits, monitoring and record keeping are also included. Examples of the simplified approach are presented for five types of retail establishments: butcher, grocery, bakery, fish and ice cream shop.